The Paretian Procrustean bed: essay on the dynamics of intervention in the supplementary health sector - Ruettimann, João Daniel (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2019)
The article intends to clarify the root cause of problems in the Brazilian health sector derived from interventionist policies set by its regulatory agencies. By assessing the contextual and historical reasons identified for the origin of said institutional bodies, the author seeks to examine the philosophical and economic theorems that undergird the policies that affect this specific market. Thus, the author makes a critic comparison of the neoclassical Paretian models of static allocative efficiency, contrasted with insights provided by the Austrian School of Economics concerning the negative unintended consequences that characterize the dynamic of interventionism.